Galectin-3-Binding Protein Inhibits Extracellular Heparan 6-O-Endosulfatase Sulf-2 - Panigrahi, Aswini; Benicky, Julius; Aljuhani, Reem; Mukherjee, Pritha; Nováková, Zora; Bařinka, Cyril; Goldman, Radoslav (Molecular & cellular proteomics : MCP, 2024)
Human extracellular 6-O-endosulfatases Sulf-1 and Sulf-2 are the only enzymes that post-synthetically alter the 6-O sulfation of heparan sulfate proteoglycans (HSPG), which regulates interactions of HSPG with many proteins. Oncogenicity of Sulf-2 in different cancers has been documented, and we have shown that Sulf-2 is associated with poor survival outcomes in head and neck squamous cell carcinoma (HNSCC). Despite its importance, limited information is available on direct protein-protein interactions of the Sulf-2 protein in the tumor microenvironment. In this study, we used monoclonal antibody (mAb) affinity purification and mass spectrometry to identify galectin-3-binding protein (LG3BP) as a highly specific binding partner of Sulf-2 in the conditioned media of HNSCC cell lines. We validated their direct interaction in vitro using recombinant proteins and have shown that the chondroitin sulfate (CS) covalently bound to the Sulf-2 influences the binding to LG3BP. We confirmed the importance of the CS chain for the interaction by generating a mutant Sulf-2 protein that lacks the CS. Importantly, we have shown that the LG3BP inhibits Sulf-2 activity in vitro in a concentration-dependent manner. As a consequence, the addition of LG3BP to a spheroid cell culture inhibited the invasion of the HNSCC cells into Matrigel. Thus, Sulf-2 interaction with LG3BP may regulate the physiological activity of the Sulf-2 enzyme as well as its activity in the tumor microenvironment.
Keywords: nádory hlavy a krku; Tumor Microenvironment; nádorové buněčné linie; Cell Movement; nádorové mikroprostředí; spinocelulární karcinom; Protein Binding; heparansulfát proteoglykany; Chondroitin Sulfates; dlaždicobuněčné karcinomy hlavy a krku; Squamous Cell Carcinoma of Head and Neck; Head and Neck Neoplasms; Sulfotransferases; Cell Line, Tumor; sulfotransferasy; Biomarkers, Tumor; Sulfatases; Heparan Sulfate Proteoglycans; chondroitinsulfáty; nádorové biomarkery; Antigens, Neoplasm; Humans; pohyb buněk; vazba proteinů; sulfatasy; antigeny nádorové; Carcinoma, Squamous Cell; lidé